Creating the Value of Secondary and Higher Schools. The Perspective of the Resource-Based Theory and the Network Theory of the Strategic Management - Jerzy NIEMCZYK; Katarzyna WOŁOWIEC; Damian TALAR (Communications of International Proceedings, 2021)
The publication aims to present the ways of creating the value of secondary and higher schools under the perspective of two strategic management theories: the Resource-Based Theory and the Network Theory. The research embraced a critical analysis of the subject literature and a survey conducted among respondents from high schools and universities using a questionnaire. The result of the study is the identification of possible directions for creating the value of secondary and higher schools. These results may constitute recommendations for managers of secondary and higher education institutions.
Keywords: Management; Education; Management of Universities